Powers - Le Guin, Ursula K., 1929- (Orlando : Harcourt, 2007)
When young Gavir's sister is brutally killed, he escapes from slavery and sets out to explore the world and his own psychic abilities.
Booklist
Kliatt
Horn Book Guide
Bulletin of the Center for Children's Books
14-19.
9-12.